PENERAPAN STRATEGI INKUIRI BIOLOGIUNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VISD NEGERI 009 AIR EMAS - Puryadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low science (IPA) learning outcomes of students, as evidenced by the fact that out of 40 students, only 20 students achieved learning mastery and the average student score was 59.50. This research was conducted as a classroom action research in two cycles. The data used in this study consisted of teacher activities, student activities, and student learning outcomes. Based on the research results, it was revealed that the inquiry-based biology learning strategy could improve students’ science learning outcomes. This improvement was evidenced by: (a) increased teacher and student activities in each cycle, where teacher activity increased from 42.00% in the first meeting of cycle I to 52.00% in the second meeting of cycle I, then to 65.00% in the first meeting of cycle II, and finally to 78.00% in the second meeting of cycle II, while student activity increased from 49.00% in the first meeting of cycle I to 61.00% in the second meeting of cycle I, then to 68.00% in the first meeting of cycle II, and to 81.00% in the second meeting of cycle II; and (b) improved completeness of student learning outcomes in each cycle, where the number of students achieving mastery increased from 20 students (50.00%) in the preliminary data to 26 students (65.00%) in the first cycle and to 34 students (85.00%) in the second cycle. In addition, students’ average learning scores also improved from 59.50 in the preliminary data to 64 in the first cycle and to 68 in the second cycle.